A STUDY ON OCCUPATIONAL STRESS AMONG THE DOCTORS WHILE ENGAGING THE COVID-19 TREATMENTS - Shanthini, B.N.; Gajenderan, Vijayakumar; B, Hariswaran (International Journal of Research -GRANTHAALAYAH, 2021)
The present paper's focuses to measure the occupational stress among professional doctors while engaging the COVID-19 treatments in the study area. The pandemic of Coronavirus in India is element of the pandemic globally caused by the ruthless sensitive respiratory syndrome virus. The COVID-19 outburst has created fear, distress, anxiety, and depression amongst the doctors and the universal public. Doctors are predominantly prone to increase various mental health disorders than the general population.. The study exercised both primary and secondary data. The secondary data was collected related to Covid-19 diseases, treatments of doctors. The primary data obtained from the doctors are engaging the COVID 19 treatments. The sample size of the study is 353. The collected responses were converted into excel sheets and converted into SPSS software version 21 for analysis. The study used simple frequency distribution and t-test for testing the framed hypothesis. The study found that the doctors engaging covid-19 treatment, first six months, and 58% of the doctors have high-level stress level. The study also found that the government hospital doctors significantly affected work culture while engaging the COVID-19 treatments in hospitals. The study confirmed that the government hospital doctors could not manage their work-life balance. The doctor has significantly affected their personal life and leads to occupational stress while engaging the COVID-19 treatments in the study area.